Requirement of DNA Polymerase η for Error-Free Bypass of UV-Induced CC and TC Photoproducts - Yu, Sung-Lim (American Society for Microbiology, 2001)
The yeast RAD30-encoded DNA polymerase η (Polη) bypasses a cis-syn thymine-thymine dimer efficiently and accurately. Human DNA polymerase η functions similarly in the bypass of this lesion, and mutations in human Polη result in the cancer prone syndrome, the variant form of xeroderma pigmentosum. UV light, however, also elicits the formation of cis-syn cyclobutane dimers and (6-4) photoproducts at 5′-CC-3′ and 5′-TC-3′ sites, and in both yeast and human DNA, UV-induced mutations occur primarily by 3′ C to T transitions. Genetic studies presented here reveal a role for yeast Polη in the error-free bypass of cyclobutane dimers and (6-4) photoproducts formed at CC and TC sites. Thus, by preventing UV mutagenesis at a wide spectrum of dipyrimidine sites, Polη plays a pivotal role in minimizing the incidence of sunlight-induced skin cancers in humans.